Lifestyle as cause and market: NCDs and Ayurveda care in Africa - Caroline Meier zu Biesen; Caroline Meier zu Biesen (Frontiers in Human Dynamics)
In this paper I explore how the Indian Ocean is (re-)emerging as a region in the medical practice I have been tracing—new flows of Ayurvedic medicines from India to East Africa—not only as a trade route on the transoceanic axis between India and Africa, but also as a “shared world in turmoil” in which the Indian diaspora, the Indian pharmaceutical industry, and Ayurvedic practitioners are creating new “lifestyle disease markets”. India-based pharmaceutical entrepreneurs from The Himalaya Drug Company and Charak Pharmaka are the most prominent distributors of Ayurvedic pharmaceuticals, extending their reach into Kenya through travel and Indo–African partnerships. Ayurvedic practitioners, many of whom belong to the Indian diaspora community in Kenya, as well as Kenyan therapists from the broader community, also play an important role. Their aspirations and efforts include the promotion of Ayurveda care in a variety of settings, from upscale Ayurvedic clinics to pharmacies and even slums. The “ancient Ayurveda tradition” promises to be a viable way to address the alarming rise of chronic non-communicable diseases (NCDs) on the continent such as diabetes, cancer, cardiovascular and mental disease, which are often referred to as “lifestyle diseases”. This choice of terminology suggests both agency and privilege and implies that their prevention, control, and management are amenable to behavioral changes in consumption patterns, diet, physical activity, and the use of Ayurvedic medicines. Using NCDs in Kenya as a case study, I shed light on the transformation of the Ayurvedic industry and new transnational pharmaceutical circuits through two lines of investigation. Firstly, by interrogating how formerly localized Ayurvedic producers and practitioners have become transnational entrepreneurs1 who strategically reinvent and tailor Ayurveda care as an “alternative modernity” for “modern” NCDs. Secondly, by critically exploring for which patients the attainment of a “wholesome lifestyle” and health consciousness is possible in the context of patchy chronic care infrastructure. I will provide an analysis that situates people's healing perceptions and therapists' practices within a field of possibilities shaped by health policies, the burgeoning burden of chronic disease, new market dynamics, and life conditions.